Tribo‐Induced Structural Transformation and Lubricant Dissociation at Amorphous Carbon–Alpha Olefin Interface. Issue 2 (22nd November 2018) - Li, Xiaowei; Wang, Aiying; Lee, Kwang‐Ryeol
Abstract: Amorphous carbon (a‐C) combined with a fluid lubricant is capable of providing an ultra‐low friction state and thus achieving long lifetime and reliable operation. However, the understanding of the atomistic process occurring at the sliding friction interfaces, especially the interfacial structure transformation and lubricant dissociation at different contact states, is still not well understood. Here, using reactive molecular dynamics simulation, the friction behavior of a self‐mated a‐C system composited with different alpha olefins (AOs) as lubricants is comparatively investigated, and the results present that due to the co‐existence of tribo‐induced thermal and shearing effects, AOs exhibit different physicochemical behaviors at the a‐C–a‐C interface compared to that at the a‐C surface. Although introducing AOs into a self‐mated a‐C system reduces the friction coefficient, its efficiency strongly relies on the AO variety and contact pressure. The pressure‐driven dissociation of AOs passivates the friction interface, resulting in the evolution of the primary friction mechanism from hydrodynamic lubrication to interfacial passivation that is not accessible by experimental characterization. The corresponding scission sites of different AOs are demonstrated, which enriches the fundamental understanding on sliding friction behavior and offers a comprehensive design criterion for lubricants (viscosity, chain length, and bond saturated states) and a‐C to achieve nearly frictionless sliding interface. Abstract : Introducing alpha olefins (AOs) into a self‐mated amorphous carbon sliding interface distinctly improves the friction property, but the transformation of interfacial structure and the dissociation of AOs are strongly dependent on the AOs and contact state between the a‐C and AOs, causing the difference in the underlying friction mechanism. The scission sites of AOs are disclosed to guide the design of improved lubricants.